Sexuality in aging: possibilities, desires and stereotypes - Diniz, Silvia Beatriz Moreno; Machado, Tainá Victoria; Freitas Soares Chariglione, Isabelle Patriciá (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Studies on aging have shown gaps regarding the subjective dimensions of this process. When it comes to sexuality, the experience of it is rarely addressed. This context can be a source of psychic suffering. The study aimed to understand how sexuality and aging are related. The research was carried out using a qualitative and quantitative method, with 193 participants. Data were collected online, via Google Forms, and analyzed using the Iramuteq software. Through the CHD analysis, the content was characterized into six classes, called Sexual Affective Prospects, Permanence of Feeling and Desiring, Intergenerational Contradictions, Satisfaction and Well-Being in the Future, Physical Experiences and Sexuality, and Aging in Society. The participants focused on exploring sexuality in stable relationships in old age, with little mention of gender. This can be explained by the idea of a-sexuality in old age. The predominance of women as respondents is also related, since the social value of women is linked to the ability to maintain relationships with men. There was also little pattern in the responses of the participants, which is related to the sexual revolution of recent decades. It is concluded, then, that the prospect of sexuality is linked to social factors, and it is important to explore such perspectives in future studies, and in other samples.